Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.orglett.1c01534
|View full text |Cite
|
Sign up to set email alerts
|

Aryl(TMP)iodonium Tosylate Reagents as a Strategic Entry Point to Diverse Aryl Intermediates: Selective Access to Arynes

Abstract: Arenes are broadly found motifs in societally important molecules. Access to diverse arene chemical space is critically important, and the ability to do so from common reagents is highly desirable. Aryl(TMP)iodonium tosylates provide one such access point to arene chemical space via diverse aryl intermediates. Here we demonstrate that controlling reaction pathways selectively leads to arynes with a broad scope of arenes and arynophiles (24 examples, 70% average yield) and efficient access to biologically activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…We found that 3-chlorophenyl(2′,4′,6′-trimethoxyphenyl)iodonium tosylate 1a extrudes aryne in high yield when treated with NaO t -Bu (1.5 equiv) as base in TBME at room temperature, as evidenced by quantitative formation of by-product trimethoxyphenyl iodide (TMP-I; Scheme 2 ). 7 Moreover, in the presence of 5 equivalents of furan 2a , we observed quantitative 1 H-NMR yield of cycloadduct 3a (Scheme 2 ). Aryne formation is the rate-determining step and aryne trapping is the product-determining step.…”
Section: Table 1 Comparison Of Competition Experiments ...mentioning
confidence: 76%
See 1 more Smart Citation
“…We found that 3-chlorophenyl(2′,4′,6′-trimethoxyphenyl)iodonium tosylate 1a extrudes aryne in high yield when treated with NaO t -Bu (1.5 equiv) as base in TBME at room temperature, as evidenced by quantitative formation of by-product trimethoxyphenyl iodide (TMP-I; Scheme 2 ). 7 Moreover, in the presence of 5 equivalents of furan 2a , we observed quantitative 1 H-NMR yield of cycloadduct 3a (Scheme 2 ). Aryne formation is the rate-determining step and aryne trapping is the product-determining step.…”
Section: Table 1 Comparison Of Competition Experiments ...mentioning
confidence: 76%
“…The percentage of active oxidant for m -CPBA was determined by iodometric titration prior to use. 12 (3-Chlorophenyl)(2,4,6-trimethoxyphenyl)iodonium tosylate 1a , 13 (3-chlorophenyl)(mesityl)iodonium tosylate 1b , 14 2-chloro-6-(trimethylsilyl)phenyl trifluoromethanesulfonate 1c , 15 (3-fluorophenyl)(2,4,6-trimethoxyphenyl)iodonium tosylate 1d , 13 N - tert -butyl-α-phenyl nitrone 2k , 16 N -phenylpyrrole 2l , 17 chloroazepane 2o , 18 N -Boc pyrrole 2p , 19 and aryne adducts 3a , 7 3j , 7 3k , 7 3o , 7 4a , 20 4b , 21 and 4c 22 have been previously characterized. Reactions performed above room temperature (ca.…”
mentioning
confidence: 99%
“…19 Treatment of sulfonate 44 (Ar=4-ClC 6 H 4 ) with i-PrMgCl led to the corresponding aryne, The generation of arynes can be achieved by treatment of diaryliodonium salts with alkoxides as a base via ortho-deprotonation of diaryliodonium salts (Scheme 10). [21][22][23] In the presence of NaO t Bu, the cycloaddition of aryne, generated from aryl(mesityl)iodonium tosylate salt 54, with benzyl azide was performed in tert-butyl methyl ether (TBME) at 50 °C to give a 3.8:1 mixture of regioisomers 55a and 55b in 63% combined yield. 21a In the presence of KO t Bu, the reaction of iodonium salt 56 with N-benzylbenzamide 57 at room temperature led to the higher ratio of two regioisomers 58a and 58b.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The generation of arynes can be achieved by ortho -deprotonation of diaryliodonium salts on treatment an alkoxide as a base (Scheme 10 ). 21 22 23 Treatment of aryl(mesityl)iodonium tosylate salt 54 with NaO t Bu in tert -butyl methyl ether (TBME) at 50 °C generated an aryne that underwent cycloaddition with benzyl azide to give a 3.8:1 mixture of regioisomers 55a and 55b in 63% combined yield. 21a The reaction of iodonium salt 56 with N -benzylbenzamide 57 in the presence of KO t Bu at room temperature gave two regioisomers 58a and 58b in a higher (>95:5) ratio.…”
Section: Reaction Of Precursors Activated By An Organometallic Reagen...mentioning
confidence: 99%
See 1 more Smart Citation